Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1911-3838.2011.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Management Accounting Practices in Gulf Cooperation Council Countries*

Abstract: This study examines how management accounting practices (MAPs) have been adopted and diffused by publicly listed firms in the Gulf Cooperation Council (GCC) countries. The results of our survey show that the adoption rates for MAPs in the area of cost management and strategy are low while those in the area of performance measurement are moderate. Overall, the respondents favorably perceived their success in implementing MAPs. Power and politics, not economic (or cost–benefit) reasons, were considered to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…Another reason might be related to the unfamiliarity and reluctance of the managers and companies to adopt contemporary cost management techniques. Prior studies (Joshi, Bremser, Deshmukh, & Kumar, 2011;Halbouni & Nour, 2014) have reported that some managers, particularly in developing countries, insist on using traditional techniques and are reluctant to adopt contemporary systems.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Another reason might be related to the unfamiliarity and reluctance of the managers and companies to adopt contemporary cost management techniques. Prior studies (Joshi, Bremser, Deshmukh, & Kumar, 2011;Halbouni & Nour, 2014) have reported that some managers, particularly in developing countries, insist on using traditional techniques and are reluctant to adopt contemporary systems.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Despite the benefit of contemporary MAPs, traditional MAPs remain the popular choice among today's organizations due to easiness and low execution cost (Pierce & O'Dea, 1998;Joshi, 2011;Ahmad, 2017). As found, the more modern techniques are being used as well but mainly to supplement the traditional ones, rather than replacing them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the context of developed nations, MAPs studies have been primarily concentrating on the practices of budgeting and costing, performance measurement, and a decision support system, and a number of studies (e.g., Abdel-Kader & Luther, 2006;Angelakis et al, 2010;Armitage et al, 2016;Nuhu et al, 2017;Pavlatos & Kostakis, 2015;Pavlatos & Paggios, 2008) have reported such. Meanwhile, the application of MAPs in developing countries has been deliberated in some studies (e.g., Ahmad & Leftesi, 2014;Ahmad, 2013;Ghasemi et al, 2015;Joshi, 2001;Joshi et al, 2011) and their significance in the success of organizations has been proven. In MAPs usage, however, there has been a disparity, particularly between developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Demand for management accounting information leads to inevitable changes to management accounting (Quinn, 2014;Pavlatos & Kostakis, 2015). However, the pace of such changes may be slower than changes observed in, say manufacturing operations, and it may vary across different countries (Chenhall & Langfield-Smith, 1998;Hyvönen, 2005;Joshi et al, 2011). Existing literature (Innes & Mitchell, 1992;Zairi, 1992;Atkinson et al, 1995) documents an increased interest in new accounting methods and techniques, with many success stories.…”
Section: The Fourth Streammentioning
confidence: 99%